A Review Study on the Modeling and Simulation of Solar Tower Power Plants (Journal of Solar Energy Research Updates, 2020)
Much attention has been paid to concentrating solar power technologies (CSP) in the last two decades. Among the CSP that have been developed so far are the parabolic trough, the parabolic dish, the Fresnel collectors and the solar tower. However, the most widely used of these technologies is the solar tower power plant (STPP). This review aims to summarize the state-of-the-art modeling approaches used to simulate the performances and the reliability of the STPP. The review includes the different analytical and numerical models used in literature to predict the thermal efficiency of these STPP. A general description and comparison of different CSP technologies are first provided. An overview of STPP technology, current status and a presentation of the major components including the heliostat field and the solar receiver are then highlighted. The different research works, developed on the modeling and simulation of the STPP performances and reliability, are also investigated in this review. In summary, this work presents a comprehensive review of the existing numerical and analytical models and could serve as a guideline to develop new models for future trends in solar tower power plants.